Glucocerebrosidase Involvement in Parkinson Disease and Other Synucleinopathies - Almeida, Maria R. (Frontiers in Neurology, 2012)
Mutations in the both copies (homozygous or compound heterozygous) of the gene encoding the lysosomal enzyme glucocerebrosidase, which cleaves the glycolipid glucocerebroside into glucose and ceramide causes Gaucher Disease. However, multiple independent studies have also reported an association between GBA mutations and Parkinsonism with an increased frequency of heterozygous GBA mutations in various cohorts of patients with parkinsonism and other Lewy body disorders. Furthermore, GBA mutation carriers exhibit diverse parkinsonian phenotypes and present a diffuse pattern of Lewy body distribution in the cerebral cortex. This review provides an overview of the genetic basis for this association in various diseases with dysfunction of the central nervous system in which affected individuals developed Parkinsonian symptoms. The emerging clinical, pathological and genetic studies in neuronal synucleinopathies suggest a common underlying mechanism in the etiology of these neurodegenerative disorders.